Thoughts on ISO and the Development of Terminologies in Southern Africa - Scheffer, C.J. (Lexikos, 1992)
A South African national committee of ISO's Technical Committee 37 was established during 1990. This national committee is the link between South African bodies who develop and standardise terminologies and ISO committees who standardise terminologies with a view to the quality control of products. In this article the aims of the national committee as well as an overview of resources that can help to achieve the objectives of the committee are presented. ISO has already consented to a request of the national committee that ISO and related terminological data may be put on the National Termbank (NTB). The display of this type of information on the NTB is discussed, as well as the implications for the adapting of lexical databases based on the information needs of developing societies. The advantages of the existing national facilities for users of terminologies and other lexical data as well as the effectiveness brought about by one system to exchange such data nationally and internationally are also emphasised. The implications of language policy decisions on the development of technical languages, terminologies, general lexicography and the dissemination of information will also require special attention in a new South Africa.